2022
DOI: 10.1155/2022/5425485
|View full text |Cite
|
Sign up to set email alerts
|

Plants in Anticancer Drug Discovery: From Molecular Mechanism to Chemoprevention

Abstract: Cancer is one of the primary causes of mortality globally, and the discovery of new anticancer drugs is the most important need in recent times. Natural products have been recognized as effective in fight against various diseases including cancer for over 50 years. Plants and microbes are the primary and potential sources of natural compounds to fight against cancer. Moreover, researches in the field of plant-based natural compounds have moved towards advanced and molecular level understandings from the last f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 137 publications
2
74
0
Order By: Relevance
“…All tested extracts presented a bit anticancer activity but methanol bark extract of D. malabarica showed a potent anticancer effect (48%) while doxorubicin (70%) was used as a standard anticancer drug. Although resulted from anticancer activity in D. malabarica bark extract was quite less than standard but found not to be inactive even at very low concentration (100 μ g/mL) which could be the result of remarkable polyphenols including total flavonoids and tannins consisting of antioxidant properties that may act as anticancer agents as these phytochemicals were reported earlier as anticancer compounds [ 34 ] and may be the substitute of conventional chemotherapy or however reduce its side effects, our finding may be in agreement with earlier investigations which revealed an extensive optimistic connection between diverse secondary metabolites like flavonoids, phenolics, tannins, and saponins with antioxidant and anticancer potency. It is reported that a person's diet involving polyphenols being natural antioxidants can improve health and reduce the risk of cancers [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All tested extracts presented a bit anticancer activity but methanol bark extract of D. malabarica showed a potent anticancer effect (48%) while doxorubicin (70%) was used as a standard anticancer drug. Although resulted from anticancer activity in D. malabarica bark extract was quite less than standard but found not to be inactive even at very low concentration (100 μ g/mL) which could be the result of remarkable polyphenols including total flavonoids and tannins consisting of antioxidant properties that may act as anticancer agents as these phytochemicals were reported earlier as anticancer compounds [ 34 ] and may be the substitute of conventional chemotherapy or however reduce its side effects, our finding may be in agreement with earlier investigations which revealed an extensive optimistic connection between diverse secondary metabolites like flavonoids, phenolics, tannins, and saponins with antioxidant and anticancer potency. It is reported that a person's diet involving polyphenols being natural antioxidants can improve health and reduce the risk of cancers [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Minimal Essential Medium Eagle was utilized as the culture for HeLa cells, enhanced with 5% of fetal bovine serum (FBS), 100 IU/mL of penicillin, and 100 μ g/mL of streptomycin in flasks (75 cm 2 ) and kept in 5% carbon dioxide incubator at 37°C. Then, harvested exponentially developing cells were tallied with a hemocytometer and diluted with a specific [ 34 ] medium. The cell culture was prepared with a concentration of 6 × 10 4 cells/mL and brought into 96-well plates (100 μ L/well).…”
Section: Experimental Datamentioning
confidence: 99%
“…They remain a source of effective bioactive compounds that can be utilized directly as medications. According to current estimates, the plant kingdom has about 250,000 species, from which approximately 10% of medicinal plants have been investigated or discovered for the treatment of various diseases [ 3 ]. Hence, there is a dire need to explore more hidden components in the plant kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…The primary motivation was to select the underutilized medicinal plant, which is discussed in depth in this review, along with their mode of action and potential mechanism, and could potentially be utilized in the management and prevention of metabolic disorders. This review focuses on different varieties and their important bioactive compounds that have been presented to target MS to open up new avenues for various treatments/therapies [ 3 ]. Henceforth, this review has been designed to compile the latest available ten years of scientific studies on C. fimbriata to drive the attention of experts in food and nutrition departments towards its encouraged dietary utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The agri-food industry produces a large amount of waste and residues along the entire supply chain that still contain a considerable number of bioactive compounds such as polyphenols (phenolic acids, flavonoids, proanthocyanidins, anthocyanins), saponins, tannins, alkaloids, sterols, triterpenes, peptides, and carbohydrates [ 6 , 7 ]. In recent decades, several studies have widely shown that these compounds possess various biological activities, including antioxidant, antibacterial, antifungal, antiviral, antimicrobial, antidiabetic, anticancer, antidiarrheal, antihypertensive, antimutagenic, and anti-inflammatory properties [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%